2021
DOI: 10.1186/s12915-021-00957-x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of drug-induced post-retrieval amnesia for auditory fear memories in rats

Abstract: Background Long-term memory formation is generally assumed to involve the permanent storage of recently acquired memories, making them relatively insensitive to disruption, a process referred to as memory consolidation. However, when retrieved under specific circumstances, consolidated fear memories are thought to return to a labile state, thereby opening a window for modification (e.g., attenuation) of the memory. Several interventions during a critical time frame after this destabilization se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 73 publications
4
15
0
Order By: Relevance
“…Finally, we found no effects of memory reactivation on expression of the glutamate receptor subunit GluA2 (i.e., a marker of memory destabilization, Rao-Ruiz et al, 2011;Bhattacharya et al, 2017). This is in line with recent research showing similar null findings in rats using cued fear conditioning and Shank protein as a marker of memory destabilization (Rotondo et al, 2022, see also Luyten et al (2021) for more behavioral data).…”
Section: Discussionsupporting
confidence: 92%
“…Finally, we found no effects of memory reactivation on expression of the glutamate receptor subunit GluA2 (i.e., a marker of memory destabilization, Rao-Ruiz et al, 2011;Bhattacharya et al, 2017). This is in line with recent research showing similar null findings in rats using cued fear conditioning and Shank protein as a marker of memory destabilization (Rotondo et al, 2022, see also Luyten et al (2021) for more behavioral data).…”
Section: Discussionsupporting
confidence: 92%
“…The vast majority of studies on memory reconsolidation in animal models have been conducted on Pavlovian fear conditioning memories, where a context or a cue (typically a tone or a light) is paired with a foot shock, and subsequently the memory is retrieved by the presentation of the context/cue alone [9,10]. Despite this relatively standard and simple classical conditioning paradigm, methodological variability might account for inconsistent findings in the fear-memories reconsolidation field, e.g., [61,89,90]. In drug-related studies on memory reconsolidation, methodological variability is potentially even greater, due to the mosaic nature of these studies.…”
Section: Methodological Standardization and Replicability Of Effectsmentioning
confidence: 99%
“…Although we found that intra-hippocampal rapamycin impaired reconsolidation of a covertly retrieved context memory, it is possible that this reflects a retrieval deficit, as opposed to memory erasure. Indeed, recent reports have challenged the idea that contextual and auditory fear memories in rats undergo protein synthesis-dependent reconsolidation 33 , 34 . Indeed, we observed spared freezing in rapamycin-treated rats during the early portions of the context test in the current study ( Fig.…”
Section: Discussionmentioning
confidence: 99%